Analysis of the mutual cooperation habituation program at SDN Nagrak in developing environmental awareness - Dicky Cep Taufiq; Utomo; Annisa Dzahira Shofa (Jurnal Bidang Pendidikan Dasar, 2026)
Modernization of basic education is crucial for environmental character building, yet significant gaps remain about students' environmental apathy in the real world. This qualitative case study analyzes how a structured mutual cooperation (gotong royong) program at SDN Nagrak fosters students' environmental awareness and identifies supporting and inhibiting . Data were collected through observation, documentation, and semistructured interviews with the principal, teachers, and 30 students, with data reliability ensured through triangulation. Results indicate that the program, implemented in stages across daily, weekly, monthly, and incidental dimensions, appears to transform indifferent behavior into sustainable pro-environmental actions across cognitive, affective, and psychomotor domains. Key supports include strict regulations and committee support, while barriers include learner fatigue and differences in home culture. The study concludes that structured mutual cooperation is considered supportive of fostering collective environmental awareness, although long-term optimization requires consistent, ongoing reinforcement and alignment with the home environment.